Chromium and polyphenols from cinnamon improve insulin sensitivity - Anderson, Richard A. (Proceedings of the Nutrition Society, 2008)
Naturally-occurring compounds that have been shown to improve insulin sensitivity include Cr and polyphenols found in cinnamon (Cinnamomon cassia). These compounds also have similar effects on insulin signalling and glucose control. The signs of Cr deficiency are similar to those for the metabolic syndrome and supplemental Cr has been shown to improve all these signs in human subjects. In a double-blind placebo-controlled study it has been demonstrated that glucose, insulin, cholesterol and HbA1c are all improved in patients with type 2 diabetes following Cr supplementation. It has also been shown that cinnamon polyphenols improve insulin sensitivity in in vitro, animal and human studies. Cinnamon reduces mean fasting serum glucose (18–29%), TAG (23–30%), total cholesterol (12–26%) and LDL-cholesterol (7–27%) in subjects with type 2 diabetes after 40 d of daily consumption of 1–6 g cinnamon. Subjects with the metabolic syndrome who consume an aqueous extract of cinnamon have been shown to have improved fasting blood glucose, systolic blood pressure, percentage body fat and increased lean body mass compared with the placebo group. Studies utilizing an aqueous extract of cinnamon, high in type A polyphenols, have also demonstrated improvements in fasting glucose, glucose tolerance and insulin sensitivity in women with insulin resistance associated with the polycystic ovary syndrome. For both supplemental Cr and cinnamon not all studies have reported beneficial effects and the responses are related to the duration of the study, form of Cr or cinnamon used and the extent of obesity and glucose intolerance of the subjects.